Aktivitas Ekstrak Daun Tithonia Diversifolia Terhadap Regulasi Kadar Adiponektin pada Diabetes Melitus Tikus Putih Wistar - Rondius Solfaine; Lailatul Muniroh; Wida Wahidah Mubarokah (Jurnal Sain Veteriner, 2019)
Diabetes Melitus is a group of metabolic diseases characterized by hyperglycemia due to lack of insulin secretion or insulin activity resistance. Chronic hyperglycemia in diabetes is associated with long-term damage, dysfunction, and failure of various organs, especially the kidneys, kidneys, nerves, heart and blood vessels. The purpose of this study was to analyze the activity of Adiponektin, superoxide dismutase, malondialdehyde, and glucose level in Streptozotocin-induced diabetic wistar rats. All wistar rats were divided into 4 groups, control (D0), induction group (D1), thitonia extract dose 100 mg / kg bw (D2) and catechin dose 10 mg/kg bw (D3) for 7 days. Model diabetes were used by induction of streptozotocin (Stz) at dosage 60 mg / kg bw intraperitoneally (ip) for 7 days. On the 8th day after the treatment, all groups of rats were sacrificed for blood samples for measured levels of superoxide dismutase and malondialdehyde and Adiponektine protein using Elisa technique, and measure of glucose level with calorimetry technique. Statistical analysis of data to examine differences in treatment and control was conducted by one way Anova test with a 95% confidence level (α=0.05). The results showed that there were differences in glucose levels (p = 0.020) and Adiponektin (p = 0.001) between the control and treatment groups, but there were no differences in level of MDA (p = 0.103) and SOD (p = 0.207 ) between groups. Base on the results of the study concluded that the administration of Tithonia Diversifolia leaf extract could reduce blood sugar and Adiponectin concentrations significantly (p≤0.05) in streptozotocin-induced diabetic on rats.